2006
DOI: 10.1111/j.1467-8691.2006.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Benefits and Detriments of Conflict on Team Creativity Process

Abstract: Intra-team conflict research has shown the different effects of conflict on team output, but it has not fully addressed how conflict influences the team creativity process in different task types of project teams over the project life cycle. Conflict, project life cycle, and project types are important predictors of team creativity. This paper focuses on examining the degree of conflict that the different types of project teams experienced, and more specifically this paper seeks to understand the benefits and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 39 publications
5
99
0
2
Order By: Relevance
“…In particular, conflict (especially destructive conflict) can be agonizing for team members, causing poor creativity (Chen, 2006) as well as poor decisions and process loss (Jehn, 1997). Is there a possibility that team efficacy (in the context of TMM similarity) has a role to play in minimizing intra-team conflict?…”
Section: Group and Organization Managementmentioning
confidence: 99%
“…In particular, conflict (especially destructive conflict) can be agonizing for team members, causing poor creativity (Chen, 2006) as well as poor decisions and process loss (Jehn, 1997). Is there a possibility that team efficacy (in the context of TMM similarity) has a role to play in minimizing intra-team conflict?…”
Section: Group and Organization Managementmentioning
confidence: 99%
“…According to Chen (2006), creativity in project teams is a complex social system since it involves a combination and integration of various inputs and knowledge from multiple and interdependent project team members. Although Chen's study concerned only collocated teams, the findings demonstrated from the present research show that this affirmation can be extended to GDT.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, where studies into change-oriented extrarole behaviours have extended their criterion space to include elements of innovation, voice or taking charge as part of their dependent variable (Choi, 2007) or studies into creativity that incorporated innovation and task performance into their criterion (Chen, 2006). Here, construct contamination differs from construct confusion in that researchers have openly been influenced by other constructs, often referred to them in the literature review preceding their study, and have consciously incorporated aspects of other related constructs.…”
Section: Construct Contaminationmentioning
confidence: 99%